3‐Naphthylindole Construction by Rhodium(II)‐Catalyzed Regioselective Direct Arylation of Indoles with 1‐Diazonaphthalen‐2‐(1H)‐ones. Issue 13 (10th September 2015) - Baral, Ek Raj; Lee, Yong Rok; Kim, Sung Hong
Abstract The regioselective direct 3‐arylation of indoles with 1‐diazonaphthalen‐2‐(1H)‐ones was developed by means of a rhodium(II) pivalate‐catalyzed cross‐coupling reaction. This procedure provided a variety of novel 3‐naphthylindoles in high yield. The direct coupling of benzofuran, pyrrole or furan with 1‐diazonaphthalen‐2‐(1H)‐ones afforded 2‐ or 3‐naphthyl substituted heterocycles.